2017
DOI: 10.1039/c7cp03542j
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of nanoparticle-mediated enhanced energy transfer during high-intensity focused ultrasound sonication

Abstract: In this combined experimental and theoretical research, magnetic nano-particle (mNP) mediated energy transfer due to high intensity-focused ultrasound (HIFU) sonication has been evaluated. HIFU sonications have been performed on phantoms containing three different volume percentages (0%, 0.0047%, and 0.047%) of mNPs embedded in a tissue mimicking material (TMM). A theoretical model has been developed to calculate the temperature rise in the phantoms during HIFU sonication. It is observed from theoretical calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…These structures are indeed able to enhance HIFU-associated mechanical effects, providing cavitation nuclei [48]. Furthermore, they increase the acoustic attenuation with a consequent temperature rise [51], reducing the ultrasound intensity and the exposure time required to obtain bioeffects [47].…”
Section: High Intensity Focused Ultrasoundmentioning
confidence: 99%
“…These structures are indeed able to enhance HIFU-associated mechanical effects, providing cavitation nuclei [48]. Furthermore, they increase the acoustic attenuation with a consequent temperature rise [51], reducing the ultrasound intensity and the exposure time required to obtain bioeffects [47].…”
Section: High Intensity Focused Ultrasoundmentioning
confidence: 99%
“…The ultrasonic absorption model explaining the increased heating in materials doped with magnetic nanoparticles was proposed . The authors introduced a new heat source, which was interpreted as a “phonon layer” on the border between the magnetic nanoparticles and the surrounding matrix.…”
Section: Introductionmentioning
confidence: 72%
“…The ultrasonic absorption model explaining the increased heating in materials doped with magnetic nanoparticles was proposed. 11 The authors introduced a new heat source, which was interpreted as a "phonon layer" on the border between the magnetic nanoparticles and the surrounding matrix. Ultrasonic impact with this phonon layer leads to increased heat production higher than in the case of the boundary of nonmagnetic nanoparticles and the same matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed Analysis. In our previous work [26], we have reported that the HIFU absorption in media embedded with NPs depends on the thermal processes (viscous, phonon layers, and intrinsic absorption) at the interface of metal NPs and on the physical properties (such as density) of the media embedded with NPs [27][28][29][30]. The theoretical equation for temperature rise (DT) due to HIFU attenuation is given as…”
Section: Discussionmentioning
confidence: 99%
“…T 0 bv nf a nf P 0 q nf C nf Av m e anf vnf t dt (5) where C nf is the heat capacity, b is thermal expansion coefficient, q nf is the density of medium with NPs, v nf is the sound velocity in the medium, a nf is the total attenuation, A is the area of HIFU beam, T 0 is heat wave parameter, v m is the particle velocity, and P 0 is the HIFU acoustic power. Further details can be obtained from our previous study [26]. At a constant power P 0 , the temperature rise is a function of several parameters including T 0 , C nf , b, v nf , q nf , and a nf as reported in Eq.…”
Section: Discussionmentioning
confidence: 99%